Protein Detection Methods in Proteomics Research. Issue 1 (4th February 2005) - Westermeier, Reiner; Marouga, Rita
Abstract : In proteomics research chemical as well as physical methods are used to detect proteins subsequently to their separation. Physical methods are mostly applied after chromatography. They are either based on spectroscopy like light absorption at certain wavelengths or mass determination of peptides and their fragments with mass spectrometry. Chemical methods are used after two-dimensional electrophoresis and employ staining with organic dyes, metal chelates, fluorescent dyes, complexing with silver, or pre-labeling with fluorophores. In some cases autoradiography is still used. Since all of these techniques are very different in terms of sensitivity, their usefulness for quantitative determinations varies significantly. This review will describe the various protein detection methods applied to electrophoresis gels.